Altered canalicular remodeling associated with femur fracture in mice. Issue 4 (21st June 2021) - Emami, Armaun J.; Sebastian, Aimy; Lin, Yu‐Yang; Yee, Cristal S.; Osipov, Benjamin; Loots, Gabriela G.; Alliston, Tamara; Christiansen, Blaine A.
Abstract: We previously showed that femur fracture in mice caused a reduction in bone volume at distant skeletal sites within 2 weeks post‐fracture. Osteocytes also have the ability to remodel their surrounding bone matrix through perilacunar/canalicular remodeling (PLR). If PLR is altered systemically following fracture, this could affect bone mechanical properties and increase fracture risk at all skeletal sites. In this study, we investigated whether lacunar‐canalicular microstructure and the rate of PLR are altered in the contralateral limb following femoral fracture in mice. We hypothesized that femoral fracture would accelerate PLR by 2 weeks postfracture, followed by partial recovery by 4 weeks. We used histological evaluation and high‐resolution microcomputed tomography to quantify the morphology of the lacunar‐canalicular network at the contralateral tibia, and we used quantitative real‐time polymerase chain reaction (RT‐PCR) and RNA‐seq to measure the expression of PLR‐associated genes in the contralateral femur. We found that at both 2 and 4 weeks postfracture, canalicular width was significantly increased by 18.6% and 16.6%, respectively, in fractured mice relative to unfractured controls. At 3 days and 4 weeks post‐fracture, we observed downregulation of PLR‐associated genes; RNA‐seq analysis at 3 days post‐fracture showed a deceleration of bone formation and mineralization in the contralateral limb. These data demonstrate notable canalicular changes following fracture that could affect bone mechanical properties. These findings expand our understanding of systemic effects of fracture and how biological and structural changes at distant skeletal sites may contribute to increased fracture risk following an acute injury.